Bio-inspired fluorescence probe for ultra level detection of aliphatic amines. (September 2018) - Panda, Atanu; Venkateswarlu, Sada; Reddy, Ankireddy Seshadri; Yoon, Minyoung
Abstract: The detection of trace amounts of amines is essential to mitigate toxicity and health risks. Various chemical probes have been reported for the detection of amines, which are expensive, difficult to handle, and toxic. In this study, we have developed a bio-inspired fluorescent probe for ultra-level detection of amines in liquid solution. Diatoms, which are silicified algae were used strategically for the detection of aliphatic amines. The presence of an electron-deficient moiety in diatoms improves the ability of diatoms to detect electron-rich organic amines. When an organic amine binds to the pyrolyzed diatom, enhanced photoluminescence and a color change under UV irradiation were observed. Interestingly, fluorescence analysis revealed that the diatoms can selectively detect aliphatic amines with sensitivity up to the pM level, even in the presence of other volatile organic compounds. Among the given analytes, only the electron-rich aliphatic amines significantly enhanced the fluorescence intensity. In contrast, aromatic amines and other organic solvents did not exhibit a fluorescence signal for detection. In particular, ethylenediamine (EDA) contributes the most apparent enhancement effect, with a detection limit of 116 pM. Therefore, diatoms were proved it potential as a tool for monitoring toxic organic molecules. Graphical abstract: Turn-on diatom fluorescence towards aliphatic amine binding. Highlights: Developed a bio-inspired 'turn-on' fluorescence probe, a pyrolyzed diatom, for the detection of aliphatic amines in the liquid phase. The diatom has excellent selectivity towards aliphatic amines better than aromatic amines. The sensitivity of the probe is achieved up to pM level of aliphatic amines. Facile identification of the sensing properties by visual color analysis. This low-cost material could be an attractive fluorescent probe for the detection of electron-rich molecules.